2005
DOI: 10.1016/j.vaccine.2005.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Do successful tuberculosis vaccines need to be immunoregulatory rather than merely Th1-boosting?

Abstract: Tuberculosis vaccine candidates are entering clinical studies in areas where BCG fails. This is a high risk strategy. We suggest that geographical variation in the efficacy of BCG is related to the presence in developing countries of a cross-reactive background Th2-like response, probably attributable to exposure of mother and infant to helminths and environmental mycobacteria. Such Th2-like activity can stop M. tuberculosis from being pushed into a latent state by the Th1 response, impair bactericidal functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 32 publications
0
61
1
Order By: Relevance
“…This vaccine also appears to generate CD4+ central memory T cells rather poorly, potentially compromising control of subsequent TB infection (19,20). Another factor that may underlie BCG failure is the unusually high concentrations of IL-4 that have been found in patients from developing countries (21,22). IL-4-producing Th2 cell responses may predominate in these patients due to exposure to non-tuberculous mycobacteria (NTM) and/or helminth infections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This vaccine also appears to generate CD4+ central memory T cells rather poorly, potentially compromising control of subsequent TB infection (19,20). Another factor that may underlie BCG failure is the unusually high concentrations of IL-4 that have been found in patients from developing countries (21,22). IL-4-producing Th2 cell responses may predominate in these patients due to exposure to non-tuberculous mycobacteria (NTM) and/or helminth infections.…”
Section: Resultsmentioning
confidence: 99%
“…IL-4-producing Th2 cell responses may predominate in these patients due to exposure to non-tuberculous mycobacteria (NTM) and/or helminth infections. Resultant IL-4 production and regulatory T-cell development may negatively regulate generation of Th1 type cells that could potentially contain TB infection, thereby leading to active disease and vaccine failure (12,18,(21)(22)(23). In recent mouse studies, CD4+ regulatory T-cells induced by BCG appeared to down-regulate effector T cell activity in mice infected with a virulent W-Beijing TB genotype; a finding with implications for BCG vaccination against highly virulent circulating TB strains (24).…”
Section: Resultsmentioning
confidence: 99%
“…These observations justify the hypothesis that the sigE mutant could have strong potential as a novel attenuated vaccine, since the response to its infection fits well into the proposition that the aim of a "classical" vaccine is to mimic natural infection as closely as possible, inducing a strong immune protective response without causing extensive disease (39). In addition, the lack of a Th2 response in the presence of a strong Th1 response is considered one of the essential characteristics for a new antitubercular vaccine (34)(35)(36). Moreover, the sigE mutant can be considered a good vaccine candidate since it is highly attenuated in SCID mice (27) and at the latest time points produces a significantly lower mortality than BCG in nude mice.…”
Section: Discussionmentioning
confidence: 66%
“…This could be explained by the fact that the mice used in this study received Mexico City autoclaved, but not filtered, tap water, known to contain high loads of environmental mycobacteria. Preexposure to these environmental mycobacteria probably resulted in a basal level of immunization against mycobacterial antigens, which has been hypothesized to cause poor responsiveness to BCG vaccination (34,36). Further experiments in other animal models in which the protective potential of BCG is higher than that obtainable in our model are needed to confirm the superiority of the protective potential of the sigE mutant with respect to that of BCG.…”
Section: Discussionmentioning
confidence: 89%
“…We have pointed out previously that high IL-4 levels occur in TB most often in developing countries close to the equator, particularly in low-lying areas (22). We have suggested that this is due to the combined influence of high exposure to environmental mycobacteria and to helminths, followed by high-dose challenge with M. tuberculosis (23,25).…”
Section: Discussionmentioning
confidence: 91%